Development and Characterization of Griseofulvin Nanosponges to Enhance Bioavailability: Pharmaceutical Science-Pharmaceutics - Y. Pawar, Ashish; R. Jadhav, Khanderao; Rao, Jyoti B.; Tapkir, Ashvini D.; Malpure, Prashant S.; Bachhav, Rishikesh S. (International Journal of Life Science and Pharma Research, 2022)
The pharmaceutical industries are more interested in development of novel drug delivery system to overcome the disadvantages of traditional drug delivery system. Now a days, fungal infections are increasing worldwide. Hence the demand of novel dosage form is increased with improved therapeutic effect and minimum side effect. The main aim of this study was to develop griseofulvin loaded ß -cyclodextrin based nanosponges for improving dissolution, oral bioavailability. In the present study, the griseofulvin loaded Nano sponges were prepared by emulsion solvent diffusion method. The six different formulation batches were formulated with varying concentration ratio of drug and polymer. The Preformulation study of the drug was done by UVvisible spectrophotometer. Drug, polymer and excipient compatibility studies were analyzed by FTIR studies. The prepared Nanosponges formulation was evaluated for particle size, zeta potential, polydispersity index, scanning electron microscopy and in-vitro drug release studies. The SEM studies showed the highly porous structure of griseofulvin loaded nanosponges having a sponges-like shape. The entrapment efficiency of optimized batch F4 was found to be 97.69±0.006%. The particle size and zeta potential of optimized batch F4 was found to be 488.59nm and -20.77 respectively. The in-vitro drug release of optimized batch F4 showed the maximum drug release of 75.56% in 8 hrs. The current study successfully developed griseofulvin loaded ß - cyclodextrin based nanosponges to improve dissolution rate, oral bioavailability and masking bitter taste. The polymer used in preparation of nanosponges shows efficient drug release. Griseofulvin loaded nanosponges drug delivery showed prolonged release which is beneficial for chronic fungal infection. Another advantage of formulating novel dosage forms is reduction in dose, dosing frequency and reduced side effects.